Penyuluhan Penggunaan TOGA (Taman Obat Keluarga) Untuk Pengobatan di Desa Senggigi - Nisa Isneni Hanifa; Dyke Gita Wirasisya; Raisya Hasina (Jurnal Pengabdian Magister Pendidikan IPA, 2020)
The trend of "back to nature" is inseparable from the weakness of treatment using synthetic drugs. Some of them are the side effects caused by the high cost of synthetic medicine that is not friendly to people with low economic level, so knowledge about the use of medicinal plants is very important to be owned by the community. The condition of the people of Senggigi village after the Lombok earthquake in August 2018 was under reconstruction. The land that was used for breeding and maintenance of family medicinal plants (TOGA) was destroyed and damaged. Also, public knowledge about the types of TOGA and the use of plants in the environment around the house which has medicinal properties is also lacking. The solution offered to overcome this problem is to provide knowledge about the types of TOGA and its use for health in the form of counseling to the community. This counseling is done to improve the knowledge and skills of the Senggigi villagers in the use of TOGA for health. This activity is carried out with the delivery of material and discussion, as well as the direct practice of how to process TOGA into preparations that are ready for consumption. The counseling program went well and the people of Senggigi village were very enthusiastic in the discussion. This counseling can increase the knowledge of Senggigi villagers about the use of TOGA as a family treatment seen from the increase in the average post-test score against the pre-test score.